2014
DOI: 10.1080/19382014.2014.998099
|View full text |Cite
|
Sign up to set email alerts
|

Islet adaptation to obesity and insulin resistance in WNIN/GR-Ob rats

Abstract: WNIN/GR-Ob mutant rat is a novel animal model to study metabolic syndrome (obesity, insulin resistance, hyperinsulinemia, impaired glucose tolerance and cardiovascular diseases). We have investigated the islet characteristics of obese mutants at different age groups (1, 6 and 12 months) to assess the islet changes in response to early and chronic metabolic stress. Our data demonstrates altered islet cell morphology and function (hypertrophy, fibrotic lesions, vacuolation, decreased stimulation index, increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 63 publications
(87 reference statements)
4
14
0
Order By: Relevance
“…The result showed that the levels of FINS were significantly increased in the CP group at the late stage of CP induction. Additionally, the elevated levels were similar to those reported in other studies in rats with hyperinsulinemia, 40,41 indicating that hyperinsulinemia in rats in the CP group was successfully induced. We also measured the changes in FBG levels in rats.…”
Section: Discussionsupporting
confidence: 88%
“…The result showed that the levels of FINS were significantly increased in the CP group at the late stage of CP induction. Additionally, the elevated levels were similar to those reported in other studies in rats with hyperinsulinemia, 40,41 indicating that hyperinsulinemia in rats in the CP group was successfully induced. We also measured the changes in FBG levels in rats.…”
Section: Discussionsupporting
confidence: 88%
“…Counterintuitively, we observed the presence of hyperinsulinaemia and enhanced in vivo insulin secretion response in SFA-HFD-fed mice despite β-cell dedifferentiation and reduced ex vivo islet insulin secretion; however, this may be explained by coincident inflammation. Indeed, genetic or diet-induced models of obesity contribute to both hyperinsulinaemia and pancreatic inflammation (31)(32)(33)(34)(35)(36) . Through various mechanisms, including increased fibrosis (32) or elevated islet blood perfusion (32,37) , inflammation in the pancreas can contribute to hyperinsulinaemia and downstream tissue dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…10 From 35 days of age, these mutants portray noticeable spontaneous obesity and a kinky tail. 11 With age, an exponential increase in body weight accompanied by hyperphagia, polydipsia, polyuria, and glycosuria are observed in these rats. 12 They also portray altered biochemical and metabolic features like IR, IGT, hyperinsulinemia, hypertriglyceridemia, hypercholesterolemia, hyperleptinaemia, and hypertension 11,12 with hypertrophy of the insulin-sensitive target organs.…”
Section: Introductionmentioning
confidence: 87%
“…11 With age, an exponential increase in body weight accompanied by hyperphagia, polydipsia, polyuria, and glycosuria are observed in these rats. 12 They also portray altered biochemical and metabolic features like IR, IGT, hyperinsulinemia, hypertriglyceridemia, hypercholesterolemia, hyperleptinaemia, and hypertension 11,12 with hypertrophy of the insulin-sensitive target organs. They depict accelerated aging with a shortened life span of 1.5 years and display an array of secondary complications warranting their application(s) in biomedical research, more pertinent to the area of MetS.…”
Section: Introductionmentioning
confidence: 87%